2011
DOI: 10.1021/cm200320u
|View full text |Cite
|
Sign up to set email alerts
|

Device Characteristics of Bulk-Heterojunction Polymer Solar Cells are Independent of Interfacial Segregation of Active Layers

Abstract: The ability to reverse the composition profile of active layers by delaminating and transferring P3HT:PCBM thin films has allowed us to probe directly the sole influence of interfacial segregation on solar cell device characteristics on the same device platform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
97
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(109 citation statements)
references
References 21 publications
12
97
0
Order By: Relevance
“…The enrichment layer is followed by a small depletion zone. Recent XPS, 15 19,50 and DSIMS experiments also indicated the existence of P3HT enrichment layer at the free surface; therefore, the vertical composition profile of P3HT from the present study is in good agreement with experiments. Lower surface energy of P3HT as compared to PCBM is usually mentioned as the reason for the thin enrichment layer formation.…”
Section: Resultssupporting
confidence: 89%
“…The enrichment layer is followed by a small depletion zone. Recent XPS, 15 19,50 and DSIMS experiments also indicated the existence of P3HT enrichment layer at the free surface; therefore, the vertical composition profile of P3HT from the present study is in good agreement with experiments. Lower surface energy of P3HT as compared to PCBM is usually mentioned as the reason for the thin enrichment layer formation.…”
Section: Resultssupporting
confidence: 89%
“…Effectively, the entire volume of device contributes to charge transport, regardless of processing conditions. Further, this high bulk connectivity of all three phases explains the observation by Wang et al 55 regarding contact area with electrode. They speculated that as long as contact area between fullerene and cathode is nonzero (even as low as 3%), it enables electron extraction.…”
Section: Connectivity Of Domains To Relevant Electrodes and Tortuositsupporting
confidence: 58%
“…Despite the low contrast, the authors of these studies were able to reconstruct the three-dimensional structure from a series of images taken at different tilt angles. Analysis of the 3D morphologies suggested that since less P3HT fibers were found at the top interface, the top surface was PCBM-rich; this is in direct contradiction with multiple NEXAFS and XPS experiments [11][12][13]. We surmise that two difficulties may be responsible for the apparent disagreement.…”
Section: X-ray and Electron Microscopymentioning
confidence: 56%
“…Thus, the small regions of high conduction visible in Fig. 1C could be due to regions of exposed PCBM; NEXAFS studies have determined that about 3% of PCBM exists at the air interface [12].…”
Section: Scanning Probe Microscopymentioning
confidence: 99%
See 1 more Smart Citation